Design as leverage - mapping solutions - Gago, José (2025)
Design students on their learning path need to know the different phases of a design project, from the background research until reaching the final proposals. This research developed in the context of learning, propose to introduce exploratory phases that could promote reflexivity, where students can iteratively explore various codes and patterns of information. This research focuses on identifying design literacy elements that can guide the future development of a design proposal. It aimed to develop the exploratory phase of support for the development of communication of food products of Portuguese origin for the Luxembourg market. The authors carried this research in the curricular unit of Design of Corporative Identity, Degree of Design, School of Arts of the University of Evora in the second semester of 2022/23. The Study Follows the methodologies of descriptive case study, thematic analysis and visual mapping. The present study aims to answer how a strategy combining a sensory analysis of a product and an exploratory mapping contributes to reflexivity on solutions to explore in a project. The results allowed the researchers to verify that using different visual mappings in the exploratory phases allows the students to exercise reasoning on the cultural context of the destination culture, the cultural context of the final user.